2015
DOI: 10.1108/jcs-10-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Screening for post-traumatic stress symptoms in looked after children

Abstract: Purpose: Many children who are looked after by the state have experienced adverse and traumatic life circumstances prior to being removed from their biological parents. Previous research has highlighted that many of them experience barriers to accessing psychological therapies. The purpose of this paper is to investigate the feasibility of assessing post-traumatic stress disorder (PTSD)-like symptoms using a screening tool, and through this to determine the prevalence of PTSD-like symptoms in looked after chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…In a study of looked‐after children using the CRIES‐8 as a screening instrument, Morris et al . (2015) reported that 75 per cent scored above the threshold for probable PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of looked‐after children using the CRIES‐8 as a screening instrument, Morris et al . (2015) reported that 75 per cent scored above the threshold for probable PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding is more in line with studies involving similar at-risk populations of 'justice involved' or 'looked after' children and young people. In a study of looked-after children using the CRIES-8 as a screening instrument, Morris et al (2015) reported that 75 per cent scored above the threshold for probable PTSD.…”
Section: 'Almost Half the Sample… Of Youth Screened Positively For Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…We used British data from both a general population sample and from a survey of children who had been removed from unsafe family homes and placed in foster care, and who are more vulnerable and deemed at higher risk of mental health issues, particularly PTSD. [11][12] In Britain, these children are called 'looked-after-children' (LAC) but are more commonly referred to as children-in-care, and from here on, we use the term LAC to refer to this group. We report the correlates of AA-PTSD with regard to demographics and comorbid diagnoses to explore whether there are any individual-level characteristics that may be over-or under-represented when using the different diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…These discouraging findings have prompted governments to address these concerns; positioning this population at the forefront of policy and legislation [9,10]. Yet despite being classified as a high-risk group; factors such as multiple placements, residential moves, poor screening in development and education, delays in service provision, limited data collation, consent and segregated service sectors are still suggested to contribute to these outcomes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%